2020
DOI: 10.30597/jkmm.v2i1.9420
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Stres Kerja Dan Beban Kerja Dengan Kelelahan Kerja pada Perawat di RSUDTenriawaru Kelas B Kabupaten Bone Tahun 2018

Abstract: Selama dua tahun terakhir ini RSUD Tenriawaru Kelas B Kabupaten Bone mengalami peningkatan jumlah pasien yang dibuktikan dengan Bed Occupancy Rate (BOR), hal ini membuat beban kerja para perawat semakin bertambah, semakin bertambahnya beban para perawat semakin bertambah tingkat kelelahan yang dirasakan perawat dan jika hal ini terus berlanjut akan terjadi penurunan produktivitas kerja dan dapat memicu terjadinya stres kerja. Penelitian ini bertujuan untuk menganalisis hubungan antara beban kerja dan s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…Job stress also impacts the physical condition of nurses, such as fatigue. This is supported by research by Mulfiyanti et al (2020), which states a significant relationship between work stress and fatigue. Fatigue in nurses will provide sub-optimal service quality due to nurses' changing habits, one of which is disturbed sleep patterns.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Job stress also impacts the physical condition of nurses, such as fatigue. This is supported by research by Mulfiyanti et al (2020), which states a significant relationship between work stress and fatigue. Fatigue in nurses will provide sub-optimal service quality due to nurses' changing habits, one of which is disturbed sleep patterns.…”
Section: Discussionmentioning
confidence: 66%
“…Based on research from Sulistyawati, Purnawati, and Muliarta (2019), it was found that the work stress level of nurses describes that the majority have moderate stress levels. The same research also states that nurses who experience stress 95.4% (Mulfiyanti et al, 2020). A study says that there is a relationship between job satisfaction and job stress in nurses (Tisa et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…Penyebab stres kerja pada perawat ialah berlebihnya beban kerja yang diterima perawat diakibatkan meningkatnya jumlah pasien dalam tiga bulan terakhir. (5) Rumah sakit sebagai salah satu institusi pelayanan kesehatan yang beroperasi sehari-hari, rumah sakit memegang peranan penting dalam meningkatkan kesehatan masyarakat. Peraturan Pemerintah Republik Indonesia No.…”
Section: Pendahuluanunclassified
“…Seseorang yang memiliki masa kerja lama akan menimbulkan resiko besar terkena bahaya akibat pekerjaannya ataupun lingkungan. (15)…”
Section: Pembahasan Karakteristik Respondenunclassified
“…Monotonous work routines and high work demands can be a cause of job stress or stressor for senior workers. Workers who already have old age and long working periods tend to quickly experience fatigue and stress (Rudyarti, 2020).…”
Section: Respondent Characteristicmentioning
confidence: 99%